Spinal Clear Cell Meningioma: Atypical Clinical and Radiological Manifestations - Mohammad Nasser Alsadiq; Zainab Shaker Albarbari; Fatimah Alshakhs; Muath Ali Alduayji; Shaymaa Al-Umran; Abdulrahman Alenzi (Case Reports in Surgery)
Meningioma has many subtypes with clear cell meningioma being more aggressive than other variants of meningioma and one of the rarest. We report a case of spinal clear cell meningioma that occurred in a 25-year-old lady who presented with the inability to be in the supine position. A magnetic resonance image showed an intradural mass extending from L1 to L4. Near complete excision was done. The patient had motor weakness postoperatively which improved gradually. A histopathological study showed a clear cell meningioma. In a differential diagnosis of any space-occupying lesion of the spine, clear cell meningioma should be considered though it is a rare form of meningioma due to its potential to recure. An accurate follow-up is warranted.